Abundant Life: Holistic Soteriology as Motivation for Socio-Political Engagement: A Pentecostal and Missional Perspective - Prosén, Martina (The Routledge Handbook of African Theology, 2020)
This chapter proposes a holistic model for understanding salvation as “abundant life” and suggests that such a model would promote involvement—as Christians and Pentecostals—in societal reform. It presents insights and examples from the Swedish Pentecostal movement, African Pentecostal theology, and Latin American liberation theology from the 1960s. The chapter highlights the term “holistic soteriology” and what it means to say that salvation is “abundant life.” Salvation is not just about what or whom God saves when He saves the world. Nor is it just a question of from what or to what He saves us. Rather, the question that must be asked is: Who is He who saves the world? The essence of soteriology is not about the results of salvation, cause or effect, but rather about He, Himself, because no salvation is possible without a Savior.
free